Unveiling the underlying complexities in breeding for disease resistance in crop plants: review - Pati, Rutuparna; Sandhu, Surinder; Kawadiwale, Ankita K.; Kaur, Gagandeep (Frontiers in Plant Science, 2025)
Biotic stress significantly contributes to global crop losses, posing a major threat to food security and agricultural sustainability. While conventional plant breeding techniques have successfully enhanced crop resistance to pathogens, the perpetual emergence of new pathogens and the need to develop varieties with effective, stable, and broad-spectrum resistance in the shortest feasible time remain formidable challenges. The rapid delivery of these technologies to stakeholders further underscores the urgency for innovative approaches. This review delves into the complexities of breeding for disease resistance in crop plants, tracing its historical evolution and highlighting recent advancements in genetic and genomic technologies. These advancements have significantly deepened our understanding of host-pathogen interactions, enabling the identification of key genes and mechanisms governing resistance. We aim to offer insights into how historical perspectives and cutting-edge innovations can guide breeders in designing robust resistance strategies. Ultimately, this work seeks to empower breeders with actionable knowledge and tools to address the dynamic challenges posed by pathogens, paving the way for a more resilient and adaptable agricultural landscape.